Sustainable Applications for the Valorization of Cereal Processing By-Products - Charis M. Galanakis (Foods, 2022)
This review article revises the sustainable practices and applications to valorize valuable components recovered from cereal processing by-products. After introducing cereal processing by-products, their healthy compounds, and corresponding functional properties, the article explores reutilization opportunities of by-products emphasizing specific sources (e.g., oat and wheat bran, distillers’ dried grains, etc.) and the biorefinery approach. Proteins and soluble dietary fibers such as arabinoxylans are of particular interest due to their content in the cereal processing by-products and their easy extraction based on conventional technologies such as enzyme-assisted extraction and membrane filtration. Non-thermal technologies have also been suggested to improve sustainability recovery approaches. Finally, the article discusses the different applications for the recovered high-added value compounds that span across biotechnology, foods, and bakery products.